EVALUATION ON QUALITY OF LIFE OF PATIENTS WITH LIVER CIRRHOSIS AT OUTPATIENT INSTALLATION OF Dr. SARDJITO HOSPITAL YOGYAKARTA - Nirmala Manik; Djoko Wahyono; I Dewa Putu Pramantara (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Patients with liver cirrhosis has various disease symptom disturbances which have negative effects to their quality of life.This research is observational with cross sectional method. The data recording was done concurrently; it was conducted by giving Chronic Liver Disease Questionnaire (CLDQ) to the out patients with liver cirrhosis at Dr. Sardjito Hospital Yogyakarta, who fulfilled the inclusion criteria. Independent variables in this research are age, gender, education level, disease duration, degrees of severity, and types of therapy. From 30 patients included in the inclusion criteria and had filled out the Chronic Liver Disease Questionnaire (CLDQ) in Bahasa Indonesia version, it was found out a significant difference on groups disease of severity of cirrhosis according to Child Pugh criteria, with mean score quality of life 0,029 (p < 0.05). The degrees of severity of cirrhosis disease based on Child Pugh’s criteria influence the quality of life. The severer the disease the fewer the quality of life score is. Other factors such as age, gender, education level, disease duration, and types of therapy, did not influence the quality of life.